Factors of Drug Abuse Among Teenagers and Their Solutions Study at Rokan Hilir Police Station - Syahrifan Simanjuntak, Fanwar (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
According to the Narcotics Law article 1, paragraph 1 states that narcotics are artificial substances or those derived from plants that give the effect of hallucinations, decreased awareness, and cause addiction. These drugs can cause addiction if used excessively. Other uses of these dangerous substances are painkillers and to provide calmness, so many people abuse them for other purposes. Illegal drug abuse can be subject to legal sanctions. It is common knowledge that the users of these substances are not only adults, but nowadays, many teenagers are abusing these drugs. Unfortunately, teenagers who are predicted to be the next generation of the nation have been contaminated with dangerous substances that even threaten the safety of their own lives. The type of research used by the author is juridical-sociological. By using analytical descriptive research specifications. Discussion Results: 1. Factors that influence drug abuse among adolescents in Rokan Hilir's jurisdiction are: a. Personality Factors; b. Family Factors; c. Environmental Factors. d. Education Factors, e. Economic Factors. 2. Solutions to tackle drug abuse among adolescents in the jurisdiction of Rokan Hilir, namely by: a. Increasing faith in God Almighty, b. A holistic approach involves various parties, such as family, school, government, and society; c. Anti-drug education, d. Making public service advertisements. e. Conducting public service advertisements. Making public service advertisements. e. Conducting raids and conducting intensive urine tests in schools.